Regenerative Medicine in Retina: The Future Cure - Mohan, Sunita; Nare, Siddhita; Natarajan, Sundaram; Kumaramanickavel, Govindasamy (Current Tissue Engineering (Discontinued), 2016)
Regenerative medicine (RM) possesses the ability to repair injured as well as aging cells, tissues and organs. This review discusses the recent advances, future prospects and challenges in the field of RM mainly the stem cell therapy in degenerative retinal diseases such as age related macular degeneration (AMD), retinitis pigmentosa (RP) and Stargardt disease (STGD). Stem cell lines like retinal progenitor cells, induced pluripotent stem cells, mesenchymal stem cells, embryonic stem cells and very small embryonic-like stem cells have potential application in the degenerative retinal diseases where they have the potency to regenerate the injured and damaged photoreceptors and retinal neurons ultimately restoring and enhancing the visual functions. Stem cell transplantation for AMD, RP and STGD is currently transforming from bench side research to bedside which may eventually allow the progress of the more advanced therapies. In future, stem cell therapy could be combined with bioengineered products and small molecules to produce novel therapies in the field of ophthalmology particularly in terms of visual recovery to fight against blindness.
Keywords: Stargardt disease